Identification of Business Models to Accelerate E-Bus Introduction in Uruguay - World Bank (Washington, DC, 2022)
This report is the product of the technical assistance to develop a business model to finance and scale up e-mobility in Uruguay provided by the World Bank and funded by the Mobility and Logistics (MOLO) Trust Fund. The report systematically analyzes international experiences and synthesizes them as stylized business models. Combining key learnings from other countries and an in-depth assessment of the regulatory and fiscal framework in Uruguay, the report formulates five alternative business models. In a next step, it evaluates these models under different scenarios regarding their expected financial and fiscal impacts. Combining key learnings from other countries and an in-depth assessment of the regulatory and fiscal framework in Uruguay, the report formulates five alternative business models. In a next step, it evaluates these models under different scenarios regarding their expected financial and fiscal impacts. The Uruguayan experience in terms of e-bus deployment since 2019 has shown to be effective based on an integrated assets model (Bus service providers (BSPs) own chassis, batteries, and charging stations), financed through a combination of a fleet renewal trust fund from the Municipality of Montevideo and an investment subsidy from the Government of Uruguay. Beyond the public investment subsidy, the Municipality of Montevideo trust fund for fleet renewal has managed to get financing and guarantees at a moderate interest rate, helping to mitigate the high investment cost of e-buses.